Increased Abundance of Plasmacytoid Dendritic Cells and Interferon-Alpha Induces Plasma Cell Differentiation in Patients of IgA Nephropathy - Zheng, Nuoyan; Wang, Bing; Fan, Jinjin; Luo, Ning; Kong, Qingyu; Ye, Hongjian; Zhang, Jiqin; Ming, Hongyan; Yu, Xueqing (Mediators of Inflammation, 2017)
The roles of pDC and IFN-α have not been well defined in IgA nephropathy (IgAN). In this study, we investigated the abundance of pDCs and IFN-α in IgAN patients and the response of peripheral blood mononuclear cells (PBMCs) after stimulation of the pDC-preferred TLR9 ligand CpG2216. The effects of IFN-α on plasma cell differentiation and leukocyte migration were also investigated. Here, we found that the percentages of pDCs were increased in PBMCs of IgAN patients, than in those of healthy controls. Plasma levels of IFN-α proteins and abundance of plasma cells were higher in IgAN patients than in healthy donors. Plasma IFN-α levels were positively associated with proteinuria, renal IgM deposition, and renal tubular atrophy/interstitial fibrosis grade in IgAN patients. Ex vivo activation of TLR9 on pDCs resulted in increased IFN-α production and enhanced plasma cell differentiation in IgAN patients as compared with healthy donors. IFN-α treatment led to increased plasma cell differentiation in vitro. IFN-α also significantly promoted expression of chemokines IP-10 and MCP-1 in human mesangial cells, which subsequently facilitated the transendothelial migration of human CD4+ and CD14+ cells. In conclusion, pDC and its secreted cytokine IFN-α may play important roles in pathological changes of IgA nephropathy.